2001
DOI: 10.1007/s002640100234
|View full text |Cite
|
Sign up to set email alerts
|

Muscular function and bone mass after knee arthroplasty

Abstract: We report a study of 28 women with severe primary gonarthrosis followed for 1 year. Variations in bone mineral density and in functional behaviour of knee extensors and flexors were studied before and after implantation of uncemented total knee prosthesis. A functional deficit was noted in the extensor apparatus, which increased in the first 6 months following surgery. This strength was not improved 1 year following the arthroplasty, but it was more efficient as shown by the reduction of muscle fatigue. Flexor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Analogous changes for MVC force:BM ratio were noted. Several authors reported weakness of the QF muscle on the operated limb in comparison with the contralateral side in patients with unilateral TKA [1, 4, 5, 21]. Lorentzen et al [21] found that isometric MVC force deficit of the QF muscle in the operated leg 6 months after TKA was 29% when compared with the non‐operated leg at 75° of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous changes for MVC force:BM ratio were noted. Several authors reported weakness of the QF muscle on the operated limb in comparison with the contralateral side in patients with unilateral TKA [1, 4, 5, 21]. Lorentzen et al [21] found that isometric MVC force deficit of the QF muscle in the operated leg 6 months after TKA was 29% when compared with the non‐operated leg at 75° of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 On the other hand, Berth et al, 18 in a study with patients assessed three years after TKA, have demonstrated that voluntary muscle activation improved over time, but did not reach the levels of healthy individuals. Anchuela et al 26 and Lorentzen et al 27 have also reported similar results, with greater capacity of strength production after surgery.…”
Section: Discussionmentioning
confidence: 66%
“…Several researchers have investigated the alterations in the muscle strength of individuals with OA and TKA by assessing torque. 3,13,15,18,26,27 Because peak torque represents performance at a single point of the range of motion, it might not be a good indicator of total functional capacity. Thus, muscle strength over the entire range of motion (work) and strength per unit of time (power) would be more clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other causes, stress-shielding-related bone loss in the immediate proximity of a knee prosthesis may lead to loosening of the prosthesis [1]. In addition, bone loss has been observed more peripherally both in the tibial and femoral diaphyses in association with total knee replacement operations [2][3][4][5][6]. Bone loss in the operated leg is most marked during the first post-operative year [1], while the functional performance of the operated leg remains weaker than that of the non-operated leg during the same time span [7].…”
Section: Introductionmentioning
confidence: 99%